Remote Work, Motivation, and Organizational Communication: Post-Pandemic Lived Experiences in Indonesia - Aditya Bayu Nugroho (Universitas Multimedia Nusantara, 2025)
Using Indonesia as a case study, this research examines how remote and hybrid work arrangements have impacted employee motivation and organizational communication during and after the COVID-19 pandemic. It presents the lived experiences of workers applying the Self-Determination Theory (SDT), which emphasizes autonomy, competence, and relatedness, and features in-depth interviews with ten professionals across various industries. Thematic analysis identified three prominent themes: flexibility and control of the environment (autonomy), connectedness and inclusion (relatedness), and conditional performance and digital adaptation (competence). Although remote working has led to greater autonomy and work-life integration, it has also caused issues of emotional detachment and ineffective communication, particularly in roles that require high levels of interaction and collaboration. Those findings suggest that workplace designs that meet the basic psychological needs of employees can maintain a high level of motivation and performance. This study is particularly relevant and will help to understand the overall post-pandemic organizational change better, providing practical insights for companies that want to adopt effective hybrid work policies by basing the analysis in the context of Indonesia.